The need to (climate) adapt: perceptions of German sports event planners on the imperative to address climate change - Werner, K. (Frontiers in Sports and Active Living, 2024)
Introduction: While the impact of anthropogenic climate change on sports and the subsequent need for adaptation to evolving climatic conditions are acknowledged, there remains a notable paucity of scientific inquiry within the realm of sports and sports event studies specifically addressing climate change and its ramifications for event planning and management. Existing studies predominantly stem from health, medical, weather and climate science and mostly focus on mega-events and elite athlete contexts. Moreover, they often only focus on one specific impact (e.g., extreme heat) without providing a comprehensive summary or overview of all eminent impacts, resulting risks and potential adaptation strategies. This study aims to explore how (German) sports events are impacted by climate change and identify measures for organizers to address these impacts.